2020
DOI: 10.1002/fsn3.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy supplements on the differentiation of skeletal muscle satellite cells

Abstract: To investigate the effects of the activator of AMPK and high glucose on the differentiation of mouse SMSCs, primary SMSCs were isolated from mouse extensor digitorum longus muscle and grown to near confluence (80%). Postconfluent cells were cultured in a growth medium with different inductors: AICAR, glucose, and AICAR mixed with glucose. The specific protein expressions of SMSCs, myoblasts, adipocytes, and brown adipocytes were analyzed on days 0, 3, 5, 7, and 10. The results showed treatment with AICAR in SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…SMSCs, a type of stem-like cells with myogenic and lipogenic differentiation capabilities, play an important role in the development and repair of muscle tissues. Autophagy is a key regulatory process in skeletal muscle development, regeneration, and homeostasis, which can activate the differentiation of SMSCs 18 , 32 , 33 . Different degrees of autophagy have different effects on cell metabolism, and it may also have different effects on the differentiation function of SMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…SMSCs, a type of stem-like cells with myogenic and lipogenic differentiation capabilities, play an important role in the development and repair of muscle tissues. Autophagy is a key regulatory process in skeletal muscle development, regeneration, and homeostasis, which can activate the differentiation of SMSCs 18 , 32 , 33 . Different degrees of autophagy have different effects on cell metabolism, and it may also have different effects on the differentiation function of SMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cell morphology observations, we also performed fluorescent staining of SMSC marker genes (paired box 7 [ Pax7 ], MyoD ), and according to the method of Su et al [ 22 ] with slight modifications. Immunofluorescence staining was performed on fixed cultured cells.…”
Section: Methodsmentioning
confidence: 99%
“…MHC genes are expressed in response to activated AMPK, which phosphorylates and retains class IIA HDACs outside the myonucleus [ 18 ]. A previous study found that the level of AMPK phosphorylation (Thr172), possibly indicating variation in energy, changes in response to exercise, and AICAR has been found in vitro to activate AMPK and stimulate the differentiation of skeletal muscle satellite cells and found in vivo to induce the myogenic formation of satellite cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%